Komodifikasi Da'i di Media Sosial - Mufadil, Al-Lahla Zikri; Mujib, Abdul; Rustandi, Ridwan (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to understand how the meaning of commodification of da'i on the object dimension, and the meaning of commodification of da'i on the interpretant dimension contained in the da'wah content of the Lost Youth. This research method seeks in-depth information about the commodification of preachers found on the Lost Youth Youtube channel, using a qualitative approach and constructivism paradigm. The findings of this study indicate that the Pemuda Bersat youtube channel has several da'i commodification techniques, on the sign dimension, namely entertaining and comedic da'wah skills as the preacher's capabilities on social media, on the object dimension, namely the application of symbolic da'wah as da'wah content design on social media, and the interpretant dimension, namely the change in program format construction and the preacher's pernosification as a da'wah content design on social media.